A multiscale study on gel composition of hybrid alkali-activated materials partially utilizing air pollution control residue as an activator. (February 2023) - Ahmad, Muhammad Riaz; Qian, Lan-Ping; Fang, Yi; Wang, Aiguo; Dai, Jian-Guo
Abstract: This paper provides a detailed underlying mechanism of gel composition of hybrid alkali-activated fly ash/slag (AAFS) pastes prepared by utilizing the air pollution control residue (APCr, a highly alkaline waste containing 38.3% of Na2 O content by mass) as a partial replacement (8%, 16% and 24% replacement by mass) of energy-intensive commercial sodium silicate (CSS) activator. AAFS pastes containing APCr as a partial replacement of CSS showed the strength, micromechanical and microstructure properties equivalent to the reference AAFS paste without APCr (R-0). SEM-EDS, FTIR spectral subtraction, and nanoindentation results showed that reaction products in AAFS pastes were composed of geopolymer gel (N-A-S-H), cross-linked gel (C–N-A-S-H) and alkali-activated gel (C-A-S-H) contributing to 60–66% of paste volume. Reaction products were more dominated by calcium-rich gels (C-A-S-H or C-(N)-A-S-H) as compared to N-A-S-H gel in all AAFS pastes. The heat of hydration and thermogravimetric results confirmed the slow rate of reaction of APCr-AAFS pastes at the early age but a higher rate of reaction at the silater stage which contributed to achieve a similar strength as control paste (R-0).